우라늄광상을 이용한 방사성폐기물 처분 자연유사연구와 우라늄의 지화학적 거동 - 백민훈; 주여진; 정다운; 류지훈 (자원환경지질, 2023)
In this study, we reviewed and summarized comprehensive roles and importance of natural analogue studies for demonstrating the safety and improving the reliability of the safety for the deep geological disposal of high-level radioactive waste. We also investigated domestic and foreign status of natural analogue studies in order to study and substantiate complex and various radionuclide behaviors in subsurface disposal environments. In addition, we investigated and uranium behaviors in groundwater and rock in uranium deposits including domestic uranium deposits in Ogcheon Metamorphic Belt and biogeochemical interactions in geological environments. Although there are many limitations and uncertainties in directly using the information and data for uranium behaviors obtained from uranium deposits in the disposal safety assessment, the information and data can be utilized in the disposal safety assessment and safety case construction both in qualitative and partly quantitative ways. 본 연구에서는 고준위방사성폐기물 처분안전성 입증 및 신뢰성 향상을 위한 처분자연유사연구의 역할과 중요성을 개괄적으로 조사하였다. 아울러 지하 처분환경에서 복잡하고 다양한 핵종거동을 규명하고 해석하기 위한 우라늄광상을 이용한 국내외 자연유사연구 동향을 고찰하였다. 또한 국내 옥천변성대 우라늄광상을 포함하는 우라늄광상 지하수와 암석에서의 우라늄의 거동특성과 지질환경에서의 우라늄의 생지화학적 상호작용을 조사하였다. 비록 우라늄광상에서 획득한 우라늄 거동 특성 자료들은 처분안전성평가에 직접적으로 활용하는 데는 많은 제약과 불확실성을 내포하고 있지만, 우라늄광상을 통해 획득한 자료와 정보들은 처분안전성평가와 Safety Case 구축에 정성적으로 또는 일부 정량적으로 활용될 수 있을 것이다.